The Use of AISAS Method in Telemedicine Advertisement (Sentence Case) - Anky Angga Alhudha; Winny Setyonugroho; Firman Pribadi (Jurnal KESANS : Kesehatan dan Sains, 2022)
Introduction: The COVID-19 pandemic has accelerated digitalization in the health industry, indicating a transition in services toward telemedicine. In Indonesia, telemedicine is quickly expanding in tandem with technological advancements and legal regulations, with users increasing by 700 percent in the first year of 2020. This is because telemedicine is seen as a cutting-edge approach of dealing with the COVID-19 problem. Looking at the rise of digital marketing in the company and in the current market, it is not impossible for every hospital to begin using digital marketing in every activity, using various methods such as setting up websites and setting up social media. Thus, internet technology leads an advertising company named Dentsu to introduce a new buying process, namely AISAS (Attention, Interest, Search, Action, Share). Objective: This study is intended to analyze the use of AISAS method in telemedicine advertisement. Methods: This research involved 45 respondents. Respondents consisted of social media followers from hospital social media account selected by the purposive sampling. The SEM-PLS analysis in this research was used to analyze the direct effect of social media on purchase intention based on AISAS modeling. Results and Discussion: The results of this study indicate that social media has a significant and positive effect on the attention, interest and search factors of consumers. Meanwhile attention, interest, and search don’t have a significant effect toward purchase intention. Purchase intention has a significant and positive effect on action. Action doesn’t have significant effect to share. Conclusions: This study indicated telemedicine advertisement using social media as media promotion with AISAS modelling does not increase customer’s purchase intention.